SP0036 The Role and Training Needs of Non-Medical Health Professionals Using Musculoskeletal Ultrasound for The Management of Patients with Rheumatic and Musculoskeletal Diseases. (15th July 2016) - Siddle, H.; ,
Abstract : The role of the non-medical health professional has advanced with many health professionals undertaking training and using musculoskeletal ultrasound (MSUS) to extend their scope of practice. Guidelines to support training for rheumatologists have been identified but currently there are not any recommendations to support the education and training needs of non-medical health professionals using MSUS. A EULAR Task Force was established to reach a consensus on the role and education and training needs of non-medical health professionals undertaking MSUS for the management of patients with rheumatic and musculoskeletal diseases (RMDs). Based on an extensive search of the literature and expert consensus seven points to consider were formulated encompassing the role and scope of health professionals using MSUS, including the application, feasibility and added value in daily practice, and the training and competency required by health professionals. The seven points to consider are intended to support the education and training needs for health professionals using MSUS to improve the management of patients with RMDs across Europe, in conjunction with local and national regulations. Disclosure of Interest: None declared